Computational Simulation of Sediment Motion Stability Process on Bridge Abutment Due to Crib Placement (Case Study: Harapan River, Jayapura Regency): Case Study: Harapan River, Jayapura Regency - Widyastuti, Ira; Mujiati; Jansen, Davy Ivan Robert; Yunus, Ahmad Fauzi (Rudarsko-geološko-naftni zbornik, 2024)
Erosion occurs when the flow of velocity in a channel exceeds the threshold velocity that causes the bed material to move. This phenomenon is observed in the Harapan River, resulting in significant impacts, such as riverbed lowering and narrowing due to the presence of water structures (bridge abutments) spanning across the river. The objective of this study is to investigate the sediment motion stability around bridge abutments before and after the installation of cribs in order to prevent structural failures. Sediment sampling was conducted at six points around the bridge abutments, using the Pebble Count method along zigzag paths. The grain size of the bed material was classified according to the Sturgess classification standard, and the material dispersion process was analysed using the Hjustorm curve. Design rainfall was transformed into design flood discharge, which was then simulated using the Two-Dimensional Hydrodynamic, comparing the river conditions before and after crib installation. In abutments without cribs, erosion occurred in direct contact with the abutment on the right side for each sediment grain diameter. However, in abutments with cribs, erosion still occurred, but it did not directly contact either abutment despite the presence of a crib. The crib prevented and protected the abutments from being eroded by the riverbed.